2017
DOI: 10.3390/ijms18030642
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Impacts the Expression of Runx2 Target Genes and Modulates Inflammation, Oxidative Stress and Membrane Vesicle Biogenesis Gene Networks in 143B Osteosarcoma Cells

Abstract: Osteosarcoma (OS) is an aggressive malignancy of bone affecting children, adolescents and young adults. Understanding vitamin D metabolism and vitamin D regulated genes in OS is an important aspect of vitamin D/cancer paradigm, and in evaluating vitamin D as adjuvant therapy for human OS. Vitamin D treatment of 143B OS cells induced significant and novel changes in the expression of genes that regulate: (a) inflammation and immunity; (b) formation of reactive oxygen species, metabolism of cyclic nucleotides, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Hence, BMP1 involves in the activation of the TGF-β and BMP signaling pathways [13]. In recent years, BMP1 upregulation may increase cancer invasiveness in gastric cancer [14], lung cancers [15], osteosarcoma [16], and colon cancer [17]. Nevertheless, to the best of our knowledge, the involvement of BMP1 in ccRCC has not understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, BMP1 involves in the activation of the TGF-β and BMP signaling pathways [13]. In recent years, BMP1 upregulation may increase cancer invasiveness in gastric cancer [14], lung cancers [15], osteosarcoma [16], and colon cancer [17]. Nevertheless, to the best of our knowledge, the involvement of BMP1 in ccRCC has not understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors, environmental stress, and inflammatory cytokines can activate p38 . Hedges et al demonstrated the involvement of p38 in VSMC migration .…”
Section: Resultsmentioning
confidence: 99%
“…How 1,25(OH) 2 D 3 causes the increased expression of α 5 β 1 integrin remains elusive, and may be linked to induction of calcification as demonstrated in VSMC through α 5 β 1 /ERK/Runx2 pathway . The interaction between Runx2 and VDR modulates the expression of many genes affecting various cellular functions including adhesion and migration . However, the direct role of VDR and its potential interactions with other coregulatory factors that may affect integrin expression is complex and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations revealed that vitamin D, including calcitriol, alone or in combination with other agents, exerts antineoplastic effects in osteosarcoma . However, the precise molecular mechanism underlying the anti‐tumor effect of calcitriol in osteosarcoma cells remains unknown.…”
mentioning
confidence: 99%
“…(8)(9)(10) Previous investigations revealed that vitamin D, including calcitriol, alone or in combination with other agents, exerts antineoplastic effects in osteosarcoma. (12)(13)(14) However, the precise molecular mechanism underlying the anti-tumor effect of calcitriol in osteosarcoma cells remains unknown. Furthermore, the anti-tumor potential of calcitriol for the treatment of osteosarcoma has not been extensively investigated in animal models.In this study, we examined the effects of calcitriol on osteosarcoma cells in vitro and in vivo using our syngeneic…”
mentioning
confidence: 99%